Anthropological Analysis in the Perspective of Ontology, Epistemology and Axiology - Corry; Ulung Napitu; Wilson Simanjuntak; Bakhrul Khair Amal (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This library research aims to examine the existence of scientists as an independent science, which has a special method and at the same time the usefulness of anthropology in people's lives. The writing approach method used is a qualitative approach with a bibliographic method. This means that in writing this article the writer collects, selects, analyzes and presents various writings sourced from various literature books and other written sources. Syntheses from various sources are presented and assembled to obtain conclusions. The results of the literature review show that anthropology as an independent science fulfills the requirements for a philosophy of science that must contain elements of ontology, epistemology and axiology. These three elements are found in anthropology because anthropology has certain methods and benefits for many people's lives, which in the subsequent development of anthropology is not only a pure science but also an applied science.